Physical Similarity Simulation of Closely Stacked Coal Seams Mined in Faulted Geological Environments: A Comprehensive Experimental Investigation - Yapeng Zhao; Liang Kong; Gaowei Hu; Peisen Zhang; Yunkai Ji (Energy Science & Engineering)
ABSTRACT The mining of closely stacked coal seams can be associated with complex stress fields, which makes mining difficult. In addition, closely stacked coal seams often coexist with faults and confined aquifers, further complicating mining activities. However, the study of closely stacked coal seams under complex geological conditions with faults (confined water) is very rare. In this study, an experimental approach was adopted to investigate the stress field and displacement field in rocks associated with closely stacked coal mining activity (complex geological conditions with faults and confined water). The materials used in the laboratory had similar physical properties to those present in the mining environment. The results showed that the overlying rock structure has three structural types and three caving forms. When the lower coal seam is mined, the collapse of the overlying strata is characterized by “caving with digging,” “no obvious periodic pressure step,” and “it is difficult to form a beam structure.” Faults function as a stress barrier, which makes it difficult for abutment pressure to cross a fault zone and form a stress concentration near the fault zone. When mining in faulted strata with confined water, there are three areas prone to water inrush, namely near the intersection with the fault zone and coal pillar, the boundary between the coal pillar and goaf, and the middle of the goaf. The research results are of great significance to the mining of closely stacked coal seams under complex geological conditions.